The Role and Clinical Potentials of Circular RNAs in Prostate Cancer - Taheri, Mohammad; Najafi, Sajad; Basiri, Abbas; Hussen, Bashdar Mahmud; Baniahmad, Aria; Jamali, Elena; Ghafouri-Fard, Soudeh (Frontiers in Oncology, 2021)
Globally, prostate cancer (PCa) is the second most commonly diagnosed cancer in men globally. Early diagnosis may help in promoting survival in the affected patients. Circular RNAs (circRNAs) are a novel class of non-coding RNAs (ncRNAs) which have been found to show extensive dysregulation in a handful of human diseases including cancers. Progressions in RNA identification techniques have provided a vast number of circRNAs exhibiting either up-regulation or down-regulation in PCa tissues compared to normal adjacent tissues. The mechanism of action is not clear for most of dysregulated circRNAs. Among them, function of a number of newly identified dysregulated circRNAs have been assessed in PCa cells. Increase in cell proliferation, migration, invasion, and metastasis have been reported for up-regulated circRNAs which suggest their role as oncogenes. On the other hand, down-regulated circRNAs have shown tumor suppressing actions in experimental studies. Furthermore, in a majority of studies, circRNAs have been found to sponge microRNAs (miRNAs), negatively regulating expression or activity of the downstream miRNAs. Additionally, they have been identified in interaction with regulatory proteins. This axis consequently regulates a signaling pathway, a tumor suppressor, or an oncogene. Easy, quick, and reliable detection of circRNAs in human body fluids also suggests their potentials as biomarker candidates for diagnosis and prediction of prognosis in PCa patients. In this review, we have discussed the role and potentials of a number of dysregulated circRNAs in PCa.